Optimal Transfer-Ordering Strategy for a Deteriorating Inventory in Declining Market - Nita H. Shah; Kunal T. Shukla (International Journal of Mathematics and Mathematical Sciences)
The retailer's optimal procurement quantity and the number of transfers from the warehouse to the display area are determined when demand is decreasing due to recession and items in inventory are subject to deterioration at a constant rate. The objective is to maximize the retailer's total profit per unit time. The algorithms are derived to find the optimal strategy by retailer. Numerical examples are given to illustrate the proposed model. It is observed that during recession when demand is decreasing, retailer should keep a check on transportation cost and ordering cost. The display units in the show room may attract the customer.